Spin-Selective Electron Transport Through Single Chiral Molecules - Safari, Mohammad Reza; Matthes, Frank; Schneider, Claus M; Ernst, Karl-Heinz; Bürgler, Daniel E (Small (Weinheim an der Bergstrasse, Germany), 2024)
The interplay between chirality and magnetism is a source of fascination among scientists for over a century. In recent years, chirality-induced spin selectivity (CISS) has attracted renewed interest. It is observed that electron transport through layers of homochiral molecules leads to a significant spin polarization of several tens of percent. Despite the abundant experimental evidence gathered through mesoscopic transport measurements, the exact mechanism behind CISS remains elusive. This study reports spin-selective electron transport through single helical aromatic hydrocarbons that are sublimed in vacuo onto ferromagnetic cobalt surfaces and examined with spin-polarized scanning tunneling microscopy (SP-STM) at a temperature of 5 K. Direct comparison of two enantiomers under otherwise identical conditions revealed magnetochiral conductance asymmetries of up to 50% when either the molecular handedness is exchanged or the magnetization direction of the STM tip or Co substrate is reversed. Importantly, the results rule out electron-phonon coupling and ensemble effects as primary mechanisms responsible for CISS.
Keywords: scanning probe microscopy; chirality; ferromagnetic substrate; CISS effect; single‐molecule studies